Impacts of Flash Flood on Livelihood and Adaptation Strategies of the Haor Inhabitants: A Study in Tanguar Haor of Sunamganj, Bangladesh (The Dhaka University Journal of Earth and Environmental Sciences, 2020)
The study evaluates the impacts of flash flood (especially 2017 massive flash flood) and explores prevailing adaptation strategies taken by haor inhabitants to subdue the impact. Primary data were collected through field visit, questionnaire survey, FGD and KII. A purposive random sampling method was applied for selecting 350 households from 10villages located in and around Tanguar Haor. The inhabitants of low-lying haor areas are extremely vulnerable to flash flood. Their coping mechanism has been strictly curved by a number of social, economic, and political factors, leading to vicious circle of debt and poverty to mohajon (money lender) and micro credit institution, perennial marginalization from haor resources by influential groups and subsequent dependency on wealthy neighbors or relatives. The haor indigent community lives with flood, suffers a loss of income and living, confronts it with food shortage and malnutrition, and survives with the circumstances by bearing considerable debt with high interest rates. This vicious circle of debt, resource loss and poverty act as a dynamic force towards their long-lasting paucity and vulnerabilities, which curve their capability to get ready, take action, and recuperate from subsequent floods, as well as any other disasters. Government should formulate combined and effectual haor management and flood management policy and implemented suitably to shield lives and livelihoods of haor inhabitants.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 8(1), 2019, P 41-51